Bible Translation for Oral Learners: For Print or Audio? - Sundersingh, Julian (The Bible translator, 2025)
Bible translation has traditionally been done for printing the translated text so that it can be preserved in a book form for use in personal reading as well as in corporate worship in the church. However, in recent times we have seen a shift in this approach as some Bible translations, especially in minority languages, are being relegated to the exclusive domain of audio rather than print. The justification appears to be the premise that oral learners prefer to use oral forms of communication rather than the written form. In many such languages a written form may not exist at all. If a decision is made that a translation is exclusively for aural reception rather than for print, should we still proceed with a text-based book-by-book approach in Bible translation or are we better off employing an audio-based story-by-story approach? This is the main question addressed in this article.